PENGEMBANGAN MEDIA FLASHCARD BERBASIS QR-CODE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SEKOLAH DASAR - Itsna Inayatul Hilmi; Ina Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study utilised a research and development (R&D) approach with the ADDIE model comprising five stages, namely Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). The subjects were 21 fifth-grade students at SDN Bancar 02, totaling 21 students. Data collection techniques include interviews, observations, questionnaires, and test sheets. This research is motivated by issues arising in classroom learning where there is insufficient support for learning media in the classroom, leading to students lacking concentration in learning and resulting in their learning outcomes to decline and their motivation to learn to decrease. The objective of this study is to improve students' learning outcomes through QR code-based flashcard learning media, which is expected to improve low student learning outcomes, particularly in the subject of environmental studies on environmental issues that threaten life. From the data analysis, obtained, the QR-code-based Flashcard media meets the criteria for feasibility, as evidenced by the final validation score of 86.6%, subject matter expert validation of 82.6%, and language expert validation of 88.8%. Additionally, in the practicality test, the teacher response questionnaire scored 98% and the student response questionnaire scored 96.19%, while the effectiveness test using test sheets yielded a result of 0.70 or 70.2%, which is moderately or sufficiently effective.